Cellulose and cellulose derivatives physico-chemical aspects and industrial applications (Woodhead Publishing Limited, 2009)
The proceedings of the Cellucon Trust conference held in Lund, Sweden, in 1993. The latest scientific advances are covered, environmental concerns and the consequent economic costs are dealt with. The papers have surprisingly wide applications across a number of industries, including food processing, pharmaceuticals, chemical processing, civil engineering and composite materials production